An abnormality in glucocorticoid receptor expression differentiates steroid responders from nonresponders in keloid disease. (28th July 2015) - Rutkowski, D.; Syed, F.; Matthews, L.C.; Ray, D.W.; McGrouther, D.A.; Watson, R.E.B.; Bayat, A.
Summary: Background: Glucocorticoids (GCs) are first‐line treatment for keloid disease (KD) but are limited by high incidence of resistance, recurrence and undesirable side‐effects. Identifying patient responsiveness early could guide therapy. Methods: Nineteen patients with KD were recruited at week 0 (before treatment) and received intralesional steroids. At weeks 0, 2 and 4, noninvasive imaging and biopsies were performed. Responsiveness was determined by clinical response and a significant reduction in vascular perfusion following steroid treatment, using full‐field laser perfusion imaging (FLPI). Responsiveness was also evaluated using (i) spectrophotometric intracutaneous analysis to quantify changes in collagen and melanin and (ii) histology to identify changes in epidermal thickness and glycosaminoglycan (GAG) expression. Biopsies were used to quantify changes in glucocorticoid receptor (GR) expression using quantitative reverse transcriptase polymerase chain reaction, immunoblotting and immunohistochemistry. Results: At week 2, the FLPI was used to separate patients into steroid responsive ( n = 12) and nonresponsive groups ( n = 7). All patients demonstrated a significant decrease in GAG at week 2 ( P < 0·05). At week 4, responsive patients exhibited significant reduction in melanin, GAG, epidermal thickness (all P < 0·05) and a continued reduction in perfusion ( P < 0·001) compared with nonresponders. Steroid‐responsive patients had increased GR expression at baseline and showed autoregulation of GR compared with nonresponders, who showed no change in GR transcription or protein. Conclusions: This is the first demonstration that keloid response to steroids can be measured objectively using noninvasive imaging. FLPI is a potentially reliable tool to stratify KD responsiveness. Altered GR expression may be the mechanism gating therapeutic response. Abstract : What's already known about this topic? Steroids are used as first‐line treatment for keloid disease, but response is variable with apparent steroid responders and nonresponders. It remains unclear whether steroid responsiveness is due to an intrinsic difference in the mechanism of the glucocorticoid receptor (GR) action or reduced sensitivity to the steroid itself. What does this study add? We show for the first time the utility of noninvasive imaging techniques in stratifying steroid responsiveness in patients treated with steroids. GR expression increased significantly in keloid tissue. Increased GR expression also correlated with an increased response to steroid treatment. Steroid responders show a significant decrease in GR transcript and protein 2 weeks after steroid treatment ( P < 0·05), which was not evident in steroid‐resistant patients.